Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

i found a equation that holds for any natural number of n and any $x_i \ne x_j$ as follows:

$$\sum\limits_{i = 1}^{n } {\prod\limits_{\substack{j = 1\\j \ne i}}^{n } {\frac{{x_i }}{{x_i - x_j }}} } = 1$$

when n=2, it is given by

$$\frac{x_1}{x_1-x_2}+\frac{x_2}{x_2-x_1}=\frac{x_1 - x_2}{x_1 - x_2} = 1$$

when n=3, it is given by

$$\frac{x_1^2}{(x_1-x_2)(x_1-x_3)}+\frac{x_2^2}{(x_2-x_1)(x_2-x_3)}+\frac{x_3^2}{(x_3-x_1)(x_3-x_2)}=1$$

But, how can I prove for general $n$?

share|improve this question
    
You're probably 90% there. I know that you know that n = 3 works. But for n = 3 write: LHS = [(x1^2(x2-x3) + x2^2(x1-x3) + x3^2(x1-x2)] / (x1-x2)(x2-x3)(x1-x3) = (1), i.e. make the denominator equal to Product(x_i - x_j). Now try the same thing for n = 4. The tricky part is this: try to notice a way in which you can cancel down (1) and your similar result for n=4 so that you can generalise. –  Adam Rubinson Nov 20 '12 at 12:02
    
Thanks for your comments. Acctually i cound't dare to try the n=4 case. Even i tried the n=3 case with the help of mathematica. :) –  Heejin Joung Nov 20 '12 at 13:27
add comment

2 Answers

up vote 14 down vote accepted

Consider the Lagrange interpolation of the polynomial $f(x)=x^{n-1}$ with interpolation points $x_1,\ldots,x_n$. We have: $$x^{n-1}=\sum_{i=1}^{n}x_i^{n-1}\prod_{j\neq i}\frac{x-x_j}{x_i-x_j},$$ so, by comparing the leading coefficients of RHS and LHS, the result follows.

share|improve this answer
    
Thanks for your comments. When $x=1$, then I get $1=\sum \prod \frac{x_i}{x_i - x_j} \prod (1 - x_j)$, where I have no idea how to remove the second prod term in the RHS... –  Heejin Joung Nov 20 '12 at 14:48
    
and.... i get $\frac{1}{\prod \limits_{j=1}^{n} (1- x_j)} = \sum \limits_{i=1}^{n} \prod \limits_{j \ne i} \frac{x_i}{x_i - x_j} -\sum \limits_{i=1}^{n} x_i \prod \limits_{j \ne i} \frac{x_i}{x_i - x_j}$..........which means $\frac{1}{\prod \limits_{j=1}^{n} (1- x_j)} + \sum \limits_{i=1}^{n} x_i \prod \limits_{j \ne i} \frac{x_i}{x_i - x_j} = 1$ ..... –  Heejin Joung Nov 20 '12 at 14:58
    
You have not to take the evaluations of both sides for a specific $x$, you have to compare the coefficients of the monomial $x^{n-1}$: in the LHS you have $1$, in the $RHS$ you have $\sum_{i=1}^{n}x_i^{n-1}\prod_{j\neq i}\frac{1}{x_i-x_j}=\sum_{i=1}^{n}\prod_{j\neq i}\frac{x_i}{x_i-x_j}$, QED. –  Jack D'Aurizio Nov 20 '12 at 17:13
    
I'm afraid that i don't get how the $x_j$ is gone in the above equation; i expected $\sum\nolimits_{i=1}^{n} x_i^{n-1} \prod \nolimits_{j \ne i} \frac{1- x_j}{x_i - x_j}$. –  Heejin Joung Nov 21 '12 at 1:06
1  
So, $x^{n-1}$ can be written as $a + a_1 x + \cdots + a_{n-1} x^{n-1}$, which means $a_{n-1} = 1$. And $a_{n-1}$ in the Lagrange inperplation polynomial is, $\sum x_i^{n-1} \prod \frac{1}{x_i-x_j}$ as you said... Wow! its proved. oh my god... Thank you so much, i really appriciate. It really helped. –  Heejin Joung Nov 23 '12 at 4:48
show 5 more comments

For $n>1$, the partial fractional decomposition of $$ \frac1z\prod_{j=1}^{n-1}\frac{z}{z-x_j} =\frac{z^{n-2}}{\prod\limits_{j=1}^{n-1}(z-x_j)} =\sum_{i=1}^{n-1}\frac{A_i}{z-x_i}\tag{1} $$ using the Heaviside method yields $$ A_i=\frac{x_i^{n-2}}{\prod\limits_{\substack{j=1\\j\ne i}}^{n-1}(x_i-x_j)} =\prod_{\substack{j=1\\j\ne i}}^{n-1}\frac{x_i}{x_i-x_j}\tag{2} $$ Combine $(1)$ and $(2)$: $$ \begin{align} \prod_{j=1}^{n-1}\frac{z}{z-x_j} &=\sum_{i=1}^{n-1}A_i\frac{z}{z-x_i}\\ &=\sum_{i=1}^{n-1}\frac{z}{z-x_i}\prod_{\substack{j=1\\j\ne i}}^{n-1}\frac{x_i}{x_i-x_j}\\ &=\sum_{i=1}^{n-1}\left(1-\frac{x_i}{x_i-z}\right)\prod_{\substack{j=1\\j\ne i}}^{n-1}\frac{x_i}{x_i-x_j}\tag{3} \end{align} $$ Set $z=x_n$ in $(3)$: $$ \prod_{j=1}^{n-1}\frac{x_n}{x_n-x_j} =\sum_{i=1}^{n-1}\prod_{\substack{j=1\\j\ne i}}^{n-1}\frac{x_i}{x_i-x_j} -\sum_{i=1}^{n-1}\prod_{\substack{j=1\\j\ne i}}^n\frac{x_i}{x_i-x_j}\tag{4} $$ Add the second term of the right side of $(4)$ to both sides: $$ \sum_{i=1}^n\prod_{\substack{j=1\\j\ne i}}^n\frac{x_i}{x_i-x_j} =\sum_{i=1}^{n-1}\prod_{\substack{j=1\\j\ne i}}^{n-1}\frac{x_i}{x_i-x_j}\tag{5} $$ Noting that the case $n=1$ follows vacuously, using $(5)$ and induction proves that $$ \sum_{i=1}^n\prod_{\substack{j=1\\j\ne i}}^n\frac{x_i}{x_i-x_j}=1\tag{6} $$

share|improve this answer
    
Thank you for your answer. It's relatively straitforward to follow up. –  Heejin Joung Nov 23 '12 at 4:53
add comment

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.